Local recurrence and metastatic disease in pheochromocytomas and sympathetic paragangliomas - Araujo-Castro, Marta; García Sanz, Iñigo; Mínguez Ojeda, César; Hanzu, Felicia; Mora, Mireia; Vicente, Almudena; Blanco Carrera, Concepción; de Miguel Novoa, Paz; López García, María del Carmen; Lamas, Cristina; Manjón-Miguélez, Laura; del Castillo Tous, María; et al. (Frontiers in Endocrinology, 2023)
Purpose: to evaluate the prevalence of recurrence among patients with pheochromocytomas and sympathetic paragangliomas (PGLs; together PPGLs) and to identify predictors of recurrence (local recurrence and/or metastatic disease).This retrospective multicenter study included information of 303 patients with PPGLs in follow-up in 19 Spanish tertiary hospitals. Recurrent disease was defined by the development of local recurrence and/or metastatic disease after initial complete surgical resection.Results: A total of 303 patients with PPGLs that underwent 311 resections were included (288 pheochromocytomas and 15 sympathetic PGLs). After a median follow-up of 4.8 years (range 1-19), 24 patients (7.9%) had recurrent disease (3 local recurrence, 17 metastatic disease and 4 local recurrence followed by metastatic disease). The median time from the diagnosis of the PPGL to the recurrence was of 11.2 months (range 0.5-174) and recurrent disease cases distributed uniformly during the follow-up period. The presence of a pathogenic variant in SDHB gene (hazard ratio [HR] 13.3, 95% CI 4.20-41.92), higher urinary normetanephrine levels (HR 1.02 per each increase in standard deviation, 95% CI 1.01-1.03) and a larger tumor size (HR 1.01 per each increase in mm, 95% CI 1.00-1.02) were independently associated with disease recurrence.The recurrence of PPGLs occurred more frequently in patients with SDHB mutations, with larger tumors and with higher urinary normetanephrine levels. Since PPGL recurrence may occur at any time after the initial PPGL diagnosis is performed, we recommend performing a strict followup in all patients with PPGLs, especially in those patients with a higher risk of recurrent disease.